Consumption, wealth, stock and housing returns: Evidence from emerging markets - Guglielmo Maria Caporale; Ricardo M. Sousa (Center for Economic Studies and ifo Institute (CESifo), 2011)
In this paper, we show, using the consumer's budget constraint, that the residuals of the trend relationship among consumption, aggregate wealth, and labour income should predict both stock returns and housing returns. We use quarterly data for a panel of 31 emerging economies and find that, when agents expect future stock returns to be higher, they will temporarily allow consumption to rise. Regarding housing returns, if housing assets are complementary to stocks, then investors react in the same way. If, however, the increase in the exposure through risky assets is achieved by lowering the share of wealth held in the form of housing (i.e., when stock and housing assets are substitutes), then they will temporarily reduce their consumption.
Keywords: E21; E44; D12; 330; consumption; wealth; stock returns; housing returns; emerging markets